ISOLATION AND ANTIBIOGRAM PATTERN OF E. COLI ISOLATES HAVING HEAVY METALS TOLERANCE - VIRENDER SINGH; P.K. CHAUHAN; SEEMA; ANKUR TYAGI; ANU KUMAR; VIVEK KUMAR. (International Journal of Pharma and Bio Sciences, 2010)
In the present study total eight heavy metal resistant E. coli were isolated from sewage of industrial effluents from waste water treatment plant of Paonta Sahib H.P. India, against chromium, copper, nickel, cadmium. All the isolates exhibited high resistance to heavy metals with minimum inhibitory concentration (MIC) for heavy metals ranging from 50 μg/ml to 450 μg/ml. All isolates showed multiple tolerances to heavy metal and were multi antibiotic resistant. Heavy Metal Tolerance Test indicated maximum microbial tolerance of E. coli (Ec-7) to Chromium (400 μg/ml) and lowest to Copper (60 μg/ml).